PROBLEMS AND PROSPECTS OF GEOMETRIC AND GRAPHIC EDUCATION AT A TECHNICAL UNIVERSITY - Otabekov Ulug’bek G’ayrat o’g’li; Rasulova Zebiniso Doniyor Qizi (Scholar Express Journal, 2024)
This article discusses the problems and prospects of graphic education at a technical university.
Keywords: Methodology; graphic education; organization of classes